The Development Assessment Instruments Reading Appreciation Primary School - alterasi; Arshad, Mahzan; Rashid MD Idris, Mohd. (Aliterasi (Jurnal Pendidikan, Bahasa, dan sastra), 2021)
The purpose of this study is to develop a reading assessment instrument that can be used by teachers to assess students' reading skills in learning Indonesian Language in elementary school. In addition, the developed instrument can also be used by teachers as a learning tool or learning strategy in reading. Among the instruments that were developed are reading appreciationassessment instruments. Reading the appreciation of this study refers to Barrett's Taxonomy of appreciation levels. The study was carried out using research and development methods. The review process consists of three phases, namely the needs analysis phase, the design and development phase, and the implementation and evaluation phase. The needs analysis phase was carried out in three elementary schools in Banda Aceh City area, involving both teachers and students from the schools. Based on the data from the needs analysis (phase 1), the study continues with the instrument design and development phase (phase 2), and after the developed instrument meets the validity and reliability’sprerequisite conditions set by theexpert and user assessments, the next phase is implementation and evaluation (phase 3). The third phase of the study was carried out in two stages, namely the implementation and evaluation of small groups/preliminary field testing (8 students) and the implementation and evaluation involving one class students/operational field testing (26 students). The results of the third phase indicate that the developed instrument of reading appreciation assessment is effective, right on the target, in accordance with the stage of students' reading ability, according to the needs of the teacher, and can be used by the teacher as an assessment instrument and reading learning strategy.